2020
DOI: 10.32883/hcj.v5i3.845
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kelengakapan Pendokumentasian Pelayanan Kebidanan Di Wilayah Kerja Puskesmas Lubukbuaya Kota Padang

Abstract: <p><em>Midwifery documentation has a large portion in the patient's clinical record that informs certain factors or situations during the midwifery care provided. In Puskesmas Lubuk Buaya, there are 94.12% of midwives who dont report the documentation of midwifery perfectly in according to requirements that must be reported. The research aims to analyze problems related to the completeness of midwife documentation of midwifery services in the work area of Puskesmas Lubuk Buaya. The method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Factors that affect incompleteness in making medical records in their research (Nurhaidah & Harijanto, 2016) are doctors, nurses, or midwives who lack discipline, and there is no evaluation (Nurhaidah & Harijanto, 2016), supported by research (Swari et al, 2019) Factors that affect incompleteness in making medical records are factors officers, procedural factors, tools, and motivation factors (Swari et al, 2019). Research conducted by Zulfita Eka (2020) found that midwives in Lubuk Buaya Padang complete documentation only on documentation that had been templated by the Health Office, but in making service documentation with SOAP (Subjective Objective Analysis and Planning), it was incomplete, completing only for the need to collect points in order to find SKP (Professional Credit Unit) (Zulfita et al, 2020). Based on research conducted by Eka Desi Purwanti that nurses at RS Haji Jakarta found that the documentation carried out by nurses was not fully in accordance with SPO (Standard Operating Procedures) for nursing care documentation (Purwanti, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Factors that affect incompleteness in making medical records in their research (Nurhaidah & Harijanto, 2016) are doctors, nurses, or midwives who lack discipline, and there is no evaluation (Nurhaidah & Harijanto, 2016), supported by research (Swari et al, 2019) Factors that affect incompleteness in making medical records are factors officers, procedural factors, tools, and motivation factors (Swari et al, 2019). Research conducted by Zulfita Eka (2020) found that midwives in Lubuk Buaya Padang complete documentation only on documentation that had been templated by the Health Office, but in making service documentation with SOAP (Subjective Objective Analysis and Planning), it was incomplete, completing only for the need to collect points in order to find SKP (Professional Credit Unit) (Zulfita et al, 2020). Based on research conducted by Eka Desi Purwanti that nurses at RS Haji Jakarta found that the documentation carried out by nurses was not fully in accordance with SPO (Standard Operating Procedures) for nursing care documentation (Purwanti, 2012).…”
Section: Introductionmentioning
confidence: 99%